2021
DOI: 10.3390/cancers13133195
|View full text |Cite
|
Sign up to set email alerts
|

Protein Aggregation Patterns Inform about Breast Cancer Response to Antiestrogens and Reveal the RNA Ligase RTCB as Mediator of Acquired Tamoxifen Resistance

Abstract: The protein quality control network, including autophagy, the proteasome and the unfolded protein response (UPR), is triggered by stress and is overactive in acquired antiestrogen therapy resistance. We show for the first time that the aggresome load correlates with apoptosis and is increased in antiestrogen-sensitive cells compared to endocrine-resistant variants. LC-MS/MS analysis of the aggregated proteins obtained after 4OH-tamoxifen and Fulvestrant treatment identified proteins with essential function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Furthermore, protein aggregation was reported to be associated with cancer in humans: Xu et al [12] reported that aggregation processes, which involve mutant p53 protein, are associated with the development of cancer, which could thus be considered as aggregationassociated disease. This was confirmed in the research performed by other authors [13][14][15]. Another well-known fact is that the formation of amyloid aggregates in the brain was considered to lead to Parkinson's [16] and Alzheimer's [16][17][18] diseases.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, protein aggregation was reported to be associated with cancer in humans: Xu et al [12] reported that aggregation processes, which involve mutant p53 protein, are associated with the development of cancer, which could thus be considered as aggregationassociated disease. This was confirmed in the research performed by other authors [13][14][15]. Another well-known fact is that the formation of amyloid aggregates in the brain was considered to lead to Parkinson's [16] and Alzheimer's [16][17][18] diseases.…”
Section: Introductionsupporting
confidence: 66%
“…Another example is the FXR1 protein, which is involved in the regulation of memory and emotions [16]. However, protein oligomers are also known to be involved in the development of pathological processes in the body, such as cardiovascular [11] and oncological [12][13][14][15] diseases. This should be taken into account in the development of modern medical strategies aimed at correcting protein aggregation induced by the above-described factors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HIR tumors exhibit similar levels of GSH, taurine and m -inositol to other tumors, indicating similar extension of active anti-oxidative mechanisms also associated with ET resistance ( 73 ), however they are distinguished by the lowest glutamate levels (and low alanine) within the tumors, which possibly are consumed to produce GSH. UDP-GlcNAc is also upregulated in HIR but to a lesser extent than in HI tumors maintaining a relevant protein glycosylation activity; still, it is worth mentioning that endocrine resistant breast cancer cells increase their endoplasmic reticulum capacity (through the activation of unfolded protein response), which is one of the major cellular organelles where protein glycosylation occurs ( 74 , 75 ). In HIR tumors, the lowest GPC levels (within the tumors) again seems to reflect a distinct status of membrane metabolism where lower GPC may be the result of higher phospholipid (phosphatidylcholine, main membrane constituent) synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This may be specifically relevant for the luminal B subtype, where the most significant biological processes overrepresented in the high-SETD7 (mRNA) group were the ubiquitin-dependent ERAD pathway and the positive regulation of autophagy, which is also linked to the ubiquitin–proteosome system (UPS, also overrepresented). The association with high SETD7 was not strong, but given that these two pathways underly endocrine resistance [ 60 , 61 ], the additive contribution of all these genes to these processes should not be discarded. Autophagy is associated with the suppression of tumour initiation [ 62 ] and the survival of dormant BC stem cells and metastatic tumour recurrence [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%